The ethics of John Capreolus and the "nominales" - Müller, Sigrid (Verbum – Analecta Neolatina, 2004)
In his discussion about moral theology, Capreolus shows an impartial way of presenting the positions of the moderni. Capreolus was aware of the differences between the authors of this group. With respect to the notion of grace, he even regarded Aquinas’s position as a happy medium between authors who were later attributed to the via moderna. The topics touched upon on this realm were not exposed to polemics. This can be explained by the explicitly theological character of the dispute.While Capreolus’s polemics were directed against the use of theological tools in philosophical discussion, the realm of theology itself does not present a place of conflict. His discussion of moral theology does not mention voluntarism. These concepts were not part of how the moral theology of the later called via moderna was understood at the beginning of the 15th century.